A new China shock? The untold story of China's R&D subsidies - Philipp Boeing; Bettina Peters (ZEW - Leibniz Centre for European Economic Research, 2021)
China has set itself some very ambitious goals. It aims to become the world's leading nation in science and technology (S&T) before 2050. According to the 14th five-year plan, China's gross expenditures on research and development (R&D) are targeted to grow by more than 7% annually between 2021 and 2025, further increasing the current R&D-to-GDP ratio of about 2.23%. State-owned enterprises (SOEs) are likely to once again play a more prominent role in the innovation system. Importantly, they can lead state-funded research alliances with, say, small and medium-sized enterprises (SMEs) and research in-stitutions, reflecting the government's desire for both economic outcomes and political control. Serving the vision of national self-reliance, such research alliances can alleviate some of the severe scientific and technological bottlenecks that have become evident in recent years.
Keywords: 330